EPISTEMOLOGI TAFSIR ILMI DALAM TAFSIR AL-MUNTAKHAB - Arifin, M. Syamsul (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2025)
The Qur'an is a holy book that gives guidance and explanation to humans about everything (QS Al-Baqarah: 185 & An-Nahl: 89), including science and technology. There are various styles of interpretation of the Qur'an, among which is Tafsir Ilmi. Tafsir Ilmi is a style of interpreting the Qur'an with a scientific point of view that aims to reveal the truth of the miracle of the Qur'an. Tafsir ilmi seeks to explain the verses of the Qur'an using scientific theories. Among the books of interpretation that are patterned after scientific interpretation is Tafsir Al-Muntakhab compiled by Egyptian scholars who are members of the Assembly al-'A'la li ash-Syu'un al-Islamiyyah, Ministry of Religious Affairs of Egypt. This research uses a qualitative method with a type of literature study research, through a descriptive-analytical approach. The purpose of this study is to examine the epistemology of tafsir ilmi in the book of Tafsir Al-Muntakhab, related to its sources, methods and validity. Keywords: Epistemology, Tafsir Ilmi, Tafsir Al-Muntakhab